Progress Towards a Laser Produced Relativistic Electron-Positron Pair Plasma. (March 2016) - Chen, Hui; Bonlie, J.; Cauble, R.; Fiuza, F.; Goldstein, W.; Hazi, A.; Keane, C.; Link, A.; Marley, E.; Nagel, S. R.; Park, J.; Shepherd, R.; et al.
Abstract: A set of experiments has been performed exploring unique characteristics of pair jets and plasmas at several energetic short-pulse laser facilities including Titan at Livermore and OMEGA EP in Rochester, as well as the Osaka LFEX and AWE Orion lasers. New results are summarized, including positron beam emittance, scaling of pair production vs. laser energy, and initial results on the pair jet collimation using electromagnetic fields.